Mg-N-C oxygen reduction reaction catalyst and preparation and application thereof

Through the porous structure design of Mg-N-C catalyst, the problem of slow kinetics of oxygen reduction reaction in zinc-air batteries is solved, and efficient oxygen transmission and electrocatalytic activity is achieved, which is significantly better than commercial Pt/C and has a wide range of commercial applications prospect.

CN119297304APending Publication Date: 2025-01-10NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411520452.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The slow kinetic process of oxygen reduction reaction (ORR) catalyst in existing zinc-air batteries limits the commercial development of electrochemical devices. Moreover, commercial platinum-based carbon materials are costly and have low reserves, making it difficult to achieve low-cost and efficient non-precious metals. Catalyst development.

Method used

Using Mg-N-C catalyst, MgO and polymer mixed with polymer carbon and nitrogen polymer were prepared, annealed to form a porous structure, and pores were made by partial carbon reduction of MgO and metal magnesium vapor to form irregular porous carbon materials, increasing the density of active sites and Oxygen transport efficiency.

Benefits of technology

Achieve excellent ORR performance under 0.1 M KOH condition, with a half-wave potential of 0.89 V (vs. RHE), which is far better than commercial Pt/C, significantly improving electrocatalytic activity and zinc-air battery performance, reducing production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297304A_ABST
    Figure CN119297304A_ABST
Patent Text Reader

Abstract

The invention discloses an Mg-N-C oxygen reduction reaction catalyst as well as preparation and application thereof, and belongs to the technical field of battery materials. Preparing a precursor solution from a high-molecular carbon-nitrogen polymer (PVP or PANI) and MgO, drying by distillation, grinding, primary annealing, pickling and secondary annealing, providing rich carbon and nitrogen sources for the high-molecular carbon-nitrogen polymer, taking MgO as a reaction type template, reducing MgO by part of C under the action of high temperature to form Mg steam, and forming pores in the carbon template to obtain the high-molecular carbon-nitrogen polymer / MgO composite material with the high-molecular carbon-nitrogen polymer and the high-molecular carbon-nitrogen polymer / MgO composite material with the high-molecular carbon-nitrogen polymer and the high-molecular carbon-nitrogen polymer / MgO composite material. The rest of C anchors free Mg < 2 + > on a carbon skeleton to realize doping of the magnesium element, and finally, the porous stacked Mg-N-C oxygen reduction reaction catalyst is synthesized, and the catalyst material shows excellent ORR performance under an alkaline condition; after the catalyst is assembled into a zinc-air battery, the open-circuit voltage and the maximum power density of the battery are far superior to those of commercial Pt / C, and the catalyst has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a Mg-NC high-efficiency oxygen reduction reaction catalyst, a preparation method thereof, and application of the catalyst in a zinc-air battery. Background Art

[0002] Green and efficient energy conversion and storage devices, such as supercapacitors, fuel cells, metal-air batteries, etc., are widely favored by technicians in this field. Among the above energy conversion and storage devices, zinc-air batteries (ZABs) with high theoretical energy density, power density and stability have attracted much attention. The oxygen reduction reaction (ORR) involved in the discharge process and the oxygen evolution reaction (OER) involved in the charging process are two key electrochemical processes of rechargeable ZABs. The ORR reaction involves a multi-step electron transfer process and only occurs in the boundary region of the three phases of solid catalyst, liquid electrolyte and gas reactant, resulting in a relatively slow kinetic process, thus limiting the commercial development of electrochemical devices. In view of the above problems, it is crucial to develop ORR catalysts that are low-cost, highly efficient, stable and durable.

[0003] Commercial platinum (Pt)-based carbon materials are considered to be the preferred practical electrocatalysts for ORR. However, they exhibit a single catalytic activity, and the high price and low reserves of Pt severely limit the commercial application of Pt / C catalysts in rechargeable ZABs and also seriously hinder the commercialization of zinc-air batteries. Therefore, the development of low-cost, abundant, stable, and highly catalytic non-precious metal ORR catalysts is the key to solving the shortage of Pt resources, reducing the cost of dye batteries, and realizing the commercialization of fuel cells. It is also of great significance to achieve the "dual carbon" goal.

[0004] Atomically dispersed Fe-NC catalysts are considered to be one of the most promising non-platinum catalysts. Current research on high-performance Fe-NC catalysts is mainly focused on the regulation of metal-Nx active sites (such as heteroatom coordination, axial coordination, bimetallic sites, etc.), the improvement of active site density, and the construction of hierarchical porous structures. Among them, the hierarchical porous structure of the catalyst plays a vital role in the actual operation of the battery. The lack of porous structure makes most Fe-Nx active sites buried inside the dense carbon matrix, resulting in low utilization of catalytic active sites; the air, catalytic reaction substrates and products permeate and transport slowly in the battery cathode catalyst layer, resulting in serious hindrance to the kinetic reaction of the solid / liquid / gas three-phase interface. At present, most conventional methods for constructing porous structures rely on silica templates, but the removal of the template inevitably uses highly corrosive solutions (such as strong alkali, hydrofluoric acid, etc.), which are complicated, dangerous and environmentally unfriendly. It can be seen that how to more reasonably and simply increase the density of metal-Nx active sites while improving the transmission of oxygen in the catalytic layer is the key to improving the output high performance of energy devices such as zinc-air batteries. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art, to provide a Mg-NC oxygen reduction reaction catalyst, and a corresponding method for quickly and efficiently preparing the catalyst. The catalyst has high ORR performance, and its electrocatalytic performance is better than that of commercial Pt / C, and has broad market application prospects.

[0006] In order to achieve the above technical objectives, the present invention is implemented by the following technical scheme: a method for preparing a Mg-NC oxygen reduction reaction catalyst, comprising the following steps: 1) Preparation of MgO@polymer carbon nitrogen polymer precursor solution; 2) Evaporating the precursor solution and grinding it to obtain a solid precursor powder; 3) placing the precursor powder in a tube furnace and annealing to obtain a Mg-NC precursor catalyst; 4) acid-washing the Mg-NC precursor catalyst and post-treating it to obtain a solid carbon catalyst; 5) Annealing the solid carbon catalyst to obtain the final product Mg-NC catalyst.

[0007] Furthermore, in step 1), the preparation process of the precursor solution is: mixing MgO and the high molecular weight carbon nitrogen polymer, adding deionized water, stirring evenly, and standing for 3 to 6 hours; the mass ratio of MgO to the high molecular weight carbon nitrogen polymer is 1:0.5 to 4.5.

[0008] Preferably, in step 1), the high molecular weight carbon nitrogen polymer used is polyaniline or polyvinyl pyrrolidone, and the mass ratio of MgO to polyaniline is 1:0.9-1.1.

[0009] In addition to directly using MgO to prepare MgO@ polymer carbon nitrogen polymer precursor solution, MgCl 2 The specific process of reaction preparation is as follows: MgCl 2 Mix with high molecular weight carbon nitrogen polymer, add deionized water, stir evenly, add sodium hydroxide solution drop by drop, heat at 80-90℃ for 10-12 h, let stand for 3-6 h, MgCl 2 The mass ratio to the high molecular carbon nitrogen polymer is 1:0.2~1.

[0010] Furthermore, in step 2), the evaporation temperature is 80-90°C.

[0011] Furthermore, in step 3), the annealing process is carried out under an inert gas atmosphere, the annealing temperature is 850~950°C, the annealing time is 1~3 h, and the heating rate is 3~5°C / min; in step 5), the annealing process is carried out under an inert gas atmosphere, the annealing temperature is 850~950°C, the annealing time is 1~3 h, and the heating rate is 3~5°C / min.

[0012] Further, in step 4), the Mg-NC precursor catalyst is acid washed with 0.5-1 M HCl for 8-12 h.

[0013] The Mg-NC oxygen reduction reaction catalyst prepared by the above method can be used in zinc-air batteries. The Mg-NC oxygen reduction reaction catalyst is used as a cathode catalyst. In 0.1 M KOH, the catalyst exhibits excellent ORR performance.

[0014] The beneficial effects of the present invention are: 1. In the present application, a high molecular weight carbon-nitrogen polymer (PVP or PANI) and MgO are used as the main raw materials to prepare a Mg-NC catalyst. The polymer can provide abundant C and N atoms, which can more easily capture metal ions, thereby forming metal active sites. MgO, as a reactive template, can be partially reduced by carbon at high temperature to form metal magnesium vapor, thereby achieving pore formation and increasing the specific surface area of ​​the material. On the other hand, it can separate metal magnesium ions and play the role of element doping, ultimately forming a porous irregular metal-nitrogen coordinated Mg-N 4 Molecular electrocatalysts; 2. The Mg-NC catalyst prepared in this application has a rich defect structure and a multi-level pore structure, which is conducive to the exposure of more active sites, strengthens the electron transport and mass transfer process, and improves the oxygen diffusion efficiency; 3. When MgO is partially reduced by carbon at high temperature, a large number of vacancies and defects will be generated due to the volatilization of metal Mg. In the ORR electrocatalytic process, vacancies and defects are often considered to be favorable conditions, because defect engineering can be used to adjust the electronic structure of the material, thereby enriching the active and adsorption sites of the material and promoting the charge transfer and separation of the material; the metal Mg active site can effectively reduce the ORR reaction kinetic energy barrier, thereby greatly improving the ORR performance; the Mg-NC oxygen reduction electrocatalyst prepared in this application is used as an electrocatalyst material in the ORR reaction process, and exhibits excellent electrocatalytic activity performance under 0.1 M KOH alkaline conditions, and its half-wave potential can reach 0.89 V (vs. RHE), which is better than 0.84 V (vs. RHE) of 20% commercial Pt / C, greatly improving the catalytic activity of the electrocatalyst; 4. Since the Mg-NC catalyst prepared in this application exhibits excellent ORR performance, it can be used as a cathode catalyst in zinc-air batteries to accelerate oxygen reduction and improve battery performance; it has been verified that the open circuit voltage and maximum power density of the prepared battery are much better than those of commercial Pt / C, and has broad application prospects; 5. The Mg-NC catalyst disclosed in the present application is a non-precious metal catalyst with a simple preparation process and cheap and readily available raw materials, which can effectively control the production cost and provide the possibility for the expanded application of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Panels a and b are scanning electron microscope images of Mg-NC catalyst I prepared in Example 1; Figure 2 This is the ORR electrochemical performance diagram of Mg-NC catalyst I prepared in Example 1; Figure 3 The open circuit voltage diagram of the Zn-Air battery assembled using the Mg-NC catalyst I prepared in Example 1; Figure 4 The power density curve of the Zn-Air battery assembled using the Mg-NC catalyst I prepared in Example 1; Figure 5 This is the ORR electrochemical performance diagram of Mg-NC (V, VI, VII, VIII) prepared in Example 2; Figure 6 The ORR electrochemical performance diagram of Mg-NC (Ⅱ, Ⅲ, Ⅳ) prepared in Example 3; Figure 7 Schematic diagram of the ORR electrochemical performance of Mg-NC (IX, X) prepared in Example 4 and Example 5. DETAILED DESCRIPTION

[0016] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention. Example

[0017] Step 1: 0.5 g MgO and 0.5 g polyaniline (PANI) were mixed and added into a beaker containing 15 mL deionized water, stirred at room temperature for 2 h to obtain a precursor solution, and then allowed to stand for 4 h; Step 2: Place the precursor solution obtained in step 1 on a heater and evaporate to dryness at 90°C to obtain a layered solid; Step 3: Grind the layered solid obtained in step 2 to obtain a solid powder; Step 4: The solid powder was placed in an ark and then transferred to a tube furnace for annealing at 900 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to finally obtain the Mg-NC precursor catalyst; Step 5: The Mg-NC precursor catalyst obtained in the previous step was acid-washed with 1 M HCl for 12 h (to remove excess oxides), centrifuged, washed, and dried to obtain a solid carbon catalyst; Step 6: The solid carbon catalyst is subjected to secondary annealing (annealing conditions are consistent with the annealing conditions in step 4), and finally a Mg-NC catalyst is obtained, which is named Mg-NC (Ⅰ); Figure 1 This is a scanning electron microscope image of the catalyst Mg-NC (Ⅰ) prepared in this embodiment. It can be seen from the figure that the catalytic material presents a morphology of irregular porous carbon layer stacking. This is mainly because under high temperature environment, MgO@PANI reacts and MgO is partially carbonized and reduced to metallic magnesium vapor, thereby forming pores so that the catalyst presents a porous structure. On the other hand, MgO separates metallic magnesium ions and plays the role of element doping, ultimately forming a porous irregular carbon material catalyst.

[0018] Take 2 mg of Mg-NC (Ⅰ) prepared in step 6 and add it to 500 μL of dispersion to make a slurry. The dispersion is prepared by 20 μL of 0.5 wt % Nafion, 380 μL of ethanol, and 100 μL of deionized water. Take 16 μL of the slurry and evenly coat it on the surface of the glassy carbon electrode. The catalyst loading is 0.32 mg / cm 2 The potential was corrected to the reversible hydrogen electrode (RHE) potential using the Nernst equation, given by .

[0019] Zn-air battery is a fully self-assembled battery, which is coated with 1 mg / cm -2The catalyst carbon paper was used as cathode and zinc plate was used as anode. The electrolyte was 6 M KOH and 0.2 M ZnCl 2 of mixed solution.

[0020] The ORR electrochemical performance of Mg-NC (I) prepared in this example was tested. Figure 2 As shown, the half-wave potential is 0.89 V (vs. RHE) under 0.1M KOH alkaline conditions, which is much better than 0.84 V (vs. RHE) of 20% commercial Pt / C, greatly improving the ORR catalytic activity of Mg-NC.

[0021] from Figure 3 , 4 It can be seen that the open circuit voltage and maximum power density of the liquid Zn-Air battery assembled based on the catalyst Mg-NC (Ⅰ) prepared in this example are 1.5 V and 174 mW / cm 2 . Example

[0022] Step 1: 0.5 g MgO and 2 g polyvinyl pyrrolidone (PVP) were mixed and added into a beaker containing 15 mL deionized water, stirred at room temperature for 2 h to obtain a precursor solution, and allowed to stand for 4 h; Step 2: Place the precursor solution obtained in the previous step on a heater and evaporate to dryness at 90°C to obtain a layered solid; Step 3: Grinding the layered solid to obtain a solid powder; Step 4: The solid powder was divided into four groups and placed in four arks, and then transferred to a tube furnace for annealing at different temperatures (800, 850, 900, 950 °C) for 2 h in a nitrogen atmosphere with a heating rate of 5 °C / min, and finally different Mg-NC precursor catalysts were obtained; Step 5: The four groups of Mg-NC precursor catalysts prepared in step 4 were acid-washed with 1 M HCl for 12 h (to remove excess oxides), centrifuged, washed, and dried to obtain a solid carbon catalyst; Step 6: The solid carbon catalyst is subjected to secondary annealing (the annealing conditions are consistent with the annealing conditions in step 4), and finally four Mg-NC catalysts are obtained, which are named Mg-NC(V), Mg-NC(VI), Mg-NC(VII), and Mg-NC(VIII).

[0023] The ORR electrochemical performance of the Mg-NC catalysts prepared at four different annealing temperatures in this example was tested using the same test method as in Example 1. The results are shown in FIG. Figure 5As shown, the half-wave potentials of catalysts Mg-NC(V), Mg-NC(VI), Mg-NC(VII), and Mg-NC(VIII) are 0.74 V, 0.74 V, 0.87 V, and 0.80 V (vs. RHE), respectively. Example

[0024] Example 2 studied the effect of annealing temperature on catalyst performance and found that the ORR performance of the Mg-NC catalyst prepared at an annealing temperature of 900° C. was optimal. Therefore, the annealing temperature was kept at 900° C. in this example to study the effect of different MgO dosages on the performance of the prepared catalyst.

[0025] Step 1: 0.5 g, 0.7 g, 1 g MgO and 2 g PVP were mixed and added into a beaker containing 15 mL deionized water, stirred at room temperature for 2 h to obtain a precursor solution, and allowed to stand for 4 h; Step 2: Place the three groups of precursor solutions obtained in step 1 on a heater respectively, evaporate to dryness at 90°C to obtain a layered solid; Step 3: Grind the layered solid prepared in the previous step to obtain a solid powder; Step 4: The three groups of solid powders were placed in an ark respectively, and then transferred to a tube furnace, annealed at 900 °C for 2 h in a nitrogen atmosphere with a heating rate of 5 °C / min, and finally three groups of Mg-NC precursor catalysts with different ratios were obtained; Step 5: The three groups of carbon catalysts with different proportions were acid-washed with 1 M HCl for 12 h (to remove excess oxides), centrifuged, washed, and dried to obtain solid carbon catalysts; Step 6: The solid carbon catalyst obtained in the previous step is subjected to secondary annealing (annealing conditions are consistent with the annealing conditions in step 4) to obtain three groups of Mg-NC catalysts with different ratios, which are named Mg-NC (Ⅱ), Mg-NC (Ⅲ), and Mg-NC (Ⅳ); The ORR electrochemical performance of the Mg-NC oxygen reduction reaction catalyst prepared in this example was tested. Figure 6 As shown in the figure, the half-wave potentials of the catalysts Mg-NC(Ⅱ), Mg-NC(Ⅲ), and Mg-NC(Ⅳ) under alkaline conditions are 0.87 V, 0.80 V, and 0.77 V (vs. RHE), respectively. The ORR performance of the Mg-NC catalyst prepared by mixing 0.5 g MgO and 2 g PVP is the best. Example

[0026] In Examples 1 to 3, MgO is directly used as a reactive template to prepare the catalytic material by mixing with a polymer. In addition, the catalytic material can also be prepared by synthesizing MgO through a chemical reaction. The specific preparation process is as follows: Step 1: Add 2.44 g MgCl 2 Mix with 2 g PVP and add into a beaker containing 15 mL deionized water, stir at room temperature for 2 h to obtain a uniformly dispersed precursor solution, then add 0.1 M sodium hydroxide solution dropwise, react at 80 ° C for 12 h, and let stand for 4 h; Step 2: Place the precursor solution obtained in step 1 on a heater and evaporate to dryness at 90°C to obtain a layered solid; Step 3: Grind the layered solid obtained in the previous step to obtain a solid powder; Step 4: The solid powder obtained in the previous step was placed in an ark, and then transferred to a tube furnace, and annealed at 900 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a Mg-NC precursor catalyst; Step 5: The precursor catalyst obtained in step 4 is acid-washed with 1 M HCl for 12 h (to remove excess oxides), then centrifuged, washed, and dried to obtain a solid carbon catalyst; Step 6: The solid carbon catalyst obtained in the previous step is subjected to secondary annealing (annealing conditions are consistent with the annealing conditions in step 4), and finally a Mg-NC catalyst is obtained, which is named Mg-NC (Ⅸ); Example

[0027] Step 1: Add 2.44 g MgCl 2 Mix with 0.5 g PANI and add into a beaker containing 15 mL deionized water, stir at room temperature for 2 h to obtain a uniformly dispersed precursor solution, then add 0.1 M sodium hydroxide solution dropwise, react at 80 °C for 12 h, and let stand for 4 h; Step 2: Place the precursor solution obtained in step 1 on a heater and evaporate to dryness at 90°C to obtain a layered solid; Step 3: Grinding the layered solid obtained in step 2 to obtain a solid powder; Step 4: After placing the solid powder obtained in the previous step in an ark, transfer it to a tube furnace and anneal it at 900 °C for 2 h in a nitrogen atmosphere at a heating rate of 5 °C / min to obtain a Mg-NC precursor catalyst; Step 5: The precursor catalyst obtained in the previous step was acid-washed with 1 M HCl for 12 h (to remove excess oxides), centrifuged, washed, and dried to obtain a solid carbon catalyst; Step 6: The solid carbon catalyst obtained in the previous step is subjected to secondary annealing (annealing conditions are consistent with the annealing conditions in step 4), and finally a Mg-NC catalyst is obtained, which is named Mg-NC (X); The oxygen reduction reaction catalyst Mg-NC (X) prepared in Examples 4 and 5 was tested for ORR electrochemical performance. The results are as follows: Figure 7As shown, the half-wave potentials of catalysts Mg-NC(Ⅸ) and Mg-NC(Ⅹ) are 0.80 V and 0.87 V (vs. RHE), respectively.

[0028] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing a Mg-NC oxygen reduction reaction catalyst, characterized in that: The steps include: 1) Preparation of MgO@polymer carbon nitrogen polymer precursor solution; 2) Evaporating the precursor solution and grinding it to obtain a solid precursor powder; 3) placing the precursor powder in a tube furnace and annealing to obtain a Mg-NC precursor catalyst; 4) acid-washing the Mg-NC precursor catalyst and post-treating it to obtain a solid carbon catalyst; 5) Annealing the solid carbon catalyst to obtain the final product Mg-NC catalyst.

2. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 1, characterized in that: In step 1), the preparation process of the precursor solution is: MgO and the high molecular weight carbon nitrogen polymer are mixed, deionized water is added, and after stirring evenly, the mixture is allowed to stand for 3 to 6 hours.

3. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 1, characterized in that: In step 1), the preparation process of the precursor solution is: MgCl2 is mixed with a high molecular weight carbon nitrogen polymer, deionized water is added, and after stirring evenly, a sodium hydroxide solution is added dropwise, and the mixture is heated at 80-90°C for 10-12 hours and then allowed to stand for 3-6 hours.

4. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to any one of claims 2 to 3, characterized in that: In step 1), the high molecular weight carbon nitrogen polymer used to prepare the precursor solution is polyaniline or polyvinyl pyrrolidone.

5. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 4, characterized in that: In step 1), the mass ratio of MgO to the high molecular weight carbon nitrogen polymer is 1:0.5~4.

5.

6. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 4, characterized in that: In step 1), the mass ratio of MgCl2 to the high molecular weight carbon nitrogen polymer is 1:0.2~1.

7. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 4, characterized in that: In step 3), the annealing process is carried out in an inert gas atmosphere, the annealing temperature is 850~950°C, the annealing time is 1~3 h, and the heating rate is 3~5°C / min; in step 5), the annealing process is carried out in an inert gas atmosphere, the annealing temperature is 850~950°C, the annealing time is 1~3 h, and the heating rate is 3~5°C / min.

8. The method for preparing the Mg-NC oxygen reduction reaction catalyst according to claim 5, characterized in that: In step 1), the high molecular carbon nitrogen polymer used is polyaniline, and the mass ratio of MgO to polyaniline is 1:

1.

9. A Mg-NC oxygen reduction reaction catalyst, characterized in that: The invention is prepared based on the preparation method described in any one of claims 1 to 3 and 5 to 8.

10. The use of the Mg-NC oxygen reduction reaction catalyst in a zinc-air battery according to claim 9, characterized in that: Mg-NC oxygen reduction reaction catalyst was used as cathode catalyst, and the catalyst showed excellent ORR performance in 0.1 M KOH.